Clinical and hemodynamic factors in predicting response to fluid challenge during right heart catheterization. (December 2018) - Moghaddam, Nima; Swiston, John R.; Levy, Robert D.; Lee, Lisa; Huckell, Victor F.; Brunner, Nathan W.
Fluid challenge during right heart catheterization has been used for unmasking pulmonary hypertension (PH) related to left-sided heart disease. We evaluated the clinical and hemodynamic factors affecting the response to fluid challenge and investigated the role of fluid challenge in the classification and management of PH patients. We reviewed the charts of 67 patients who underwent fluid challenge with a baseline pulmonary arterial wedge pressure (PAWP) of ≤ 18 mmHg. A positive fluid challenge (PFC) was defined as an increase in PAWP to > 18 mmHg after 500 mL saline infusion. Clinical characteristics and echocardiographic and hemodynamic parameters were compared between PFC and negative fluid challenge (NFC). PFC was associated with female sex, increased BMI, and hypertension. A greater rise in PAWP was observed in PFC (6.8 ± 2.3 vs. 3.8 ± 2.7 mmHg, P = 0.001). A larger increase in PAWP correlated with a lower transpulmonary gradient (r = –0.42, P < 0.001), diastolic pulmonary gradient (r = –0.42, P < 0.001), and pulmonary vascular resistance (r = –0.38, P < 0.001). We found 100% of the patients with PFC were classified as WHO group 2 PH compared to 49% of the NFC patients ( P < 0.001). Fewer patients with PFC were started on advanced PH therapies and more were discharged from PH clinic. A PFC and the magnitude of PAWP increase after saline loading are associated with parameters related to left heart disease. In our population, fluid challenge appeared to influence the classification of PH and whether patients are started on therapy or discharged from clinic.